2020
DOI: 10.3389/fphys.2019.01527
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Jumps Preserve Skeletal Muscle Structure, Phenotype, and Myofiber Oxidative Capacity in Bed Rest

Abstract: Identification of countermeasures able to prevent disuse-induced muscle wasting is crucial to increase performance of crew members during space flight as well as ameliorate patient's clinical outcome after long immobilization periods. We report on the outcome of short but high-impact reactive jumps (JUMP) as countermeasure during 60 days of 6 • head-down tilt (HDT) bed rest on myofiber size, type composition, capillarization, and oxidative capacity in tissue biopsies (pre/post/recovery) from the knee extensor … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 109 publications
3
12
4
Order By: Relevance
“…The current analysis translated into approximately a 3-times greater number of observations compared to what is commonly found in bed rest studies (Alkner and Tesch, 2004;Trappe et al, 2007a;Blottner et al, 2020). The analyses performed indicated that the mass of the muscles involved in posture and locomotion (i.e., thigh and calf) and the function of the knee extensor muscles are the outcomes more robustly affected by bed rest, supporting previous results (Pavy-Le Traon et al, 2007).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The current analysis translated into approximately a 3-times greater number of observations compared to what is commonly found in bed rest studies (Alkner and Tesch, 2004;Trappe et al, 2007a;Blottner et al, 2020). The analyses performed indicated that the mass of the muscles involved in posture and locomotion (i.e., thigh and calf) and the function of the knee extensor muscles are the outcomes more robustly affected by bed rest, supporting previous results (Pavy-Le Traon et al, 2007).…”
Section: Discussionsupporting
confidence: 78%
“…The calf muscle area was chosen for this set of analyses because (i) it is the most consistently altered outcome measure across the studies and bed rest interventions, (ii) it is one of the outcomes with the most significant inter-individual variability, and (iii) it presents a high degree of repeatability across bed rest interventions. In addition to the observations from the current experiments, calf muscle mass is one of the most investigated outcomes in the context of bed rest (Alkner and Tesch, 2004;Trappe et al, 2007b;Salanova et al, 2015;Blottner et al, 2020). Our analyses indicated that the variability in calf muscle area changes induced by bed rest could be moderately explained by the summatory effects of all of the other variables included in the database, with "thigh muscle area, " "KE torque, "…”
Section: Discussionsupporting
confidence: 50%
“…The results, from previous publications, show that this time-efficient countermeasure attenuated the loss of whole body lean mass, leg lean mass, V . O 2peak (Kramer et al, 2017a,b), and myofiber size and phenotype (Blottner et al, 2019). While RJT had protective effects for muscle function, it could not prevent the dysregulation of glucose and lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have evoked energy related recovery‐stress states (Nicolas & Gushin, 2015; Nicolas & Weiss, 2009), cardiovascular (Platts et al., 2009; Rabineau et al., 2020) and skeletal (Hu et al., 2014; Rubin et al., 2002) adaptation mechanisms as a reaction to microgravity. Moreover, previously documented RSL‐related adaptation trends, encountering microgravity effects, include the preservation of lean body mass, prevention of partial cardiac deconditioning (Kramer, Gollhofer, et al., 2017), the structure of the skeletal muscle, preservation of phenotype and oxidative potential of the myofibres (Blottner et al., 2020). Furthermore, extensive morphological brain changes have been observed under HDTBR conditions as a result of the redistribution of brain fluid in response to changes in gravity (Roberts et al., 2015).…”
Section: Discussionmentioning
confidence: 99%